High efficiency of Mn–Ce‐modified TiO2 catalysts for the low‐temperature oxidation of Hg0 under a reducing atmosphere. (10th April 2019) - Zhang, Yingjie; Ning, Ping; Wang, Xueqian; Wang, Langlang; Ma, Yixing; Ma, Qiang; Xie, Yibing
Abstract : Manganese‐ and cerium oxide‐modified titania catalysts were prepared by the deposition precipitation for the removal of elemental mercury (Hg 0 ) from simulated yellow phosphorus off‐gas at low temperature. In addition, these catalysts were characterized by X‐ray diffraction, Brunauer–Emmett–Teller measurements, X‐ray photoelectron spectroscopy and field‐emission scanning electron microscope to determine the surface morphology of the obtained compounds and explore their formation mechanism. The results revealed that a Mn–Ce loading and reaction temperature of 10% and 150 °C, respectively, as well as a Mn/Ce molar ratio of 2:1, led to an optimal efficiency for the oxidation of elemental mercury. Furthermore, the effects of flue gas components were investigated. The presence of O2 clearly promoted the oxidation of Hg 0 . A CO atmosphere did not affect the Hg 0 oxidation, when compared with N2, whereas the presence of H2 S and water vapor inhibited the oxidation process. Furthermore, the X‐ray photoelectron spectroscopy spectra of Hg 4f revealed that the elemental mercury adsorbed by the catalyst is present as HgO. Finally, the Hg 0 catalytic oxidation mechanism was discussed on the basis of the experimental results and characterization analysis. Abstract : The simulated flue gas passed through the catalyst.The Hg 0 physically adsorbed on the catalyst surface to form adsorbed Hg 0, and then reacted with the lattice oxygen to form HgO. The consumed lattice oxygen can be supplied by the gas‐phase O2 or the Mn‐Ce mixed oxide redox cycle. There is a synergistic effect between manganese oxides and cerium oxides. The gas‐phase CO almost does not affect the oxidation of Hg 0 .